Pengaruh Pemberian Pupuk Organik Jenis Bokashi Terhadap Produktivitas Tanaman Kacang Tanah (Arachis hypogaea L.) - Sudiarti, Diah; Sholeh, David; Bukhori, Imam (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2024)
Peanuts are rich in fat, contain high protein, iron, vitamin E and calcium, vitamin B complex and phosphorus, vitamins A and K, lecithin, choline and calcium. Problems faced by local communities include low peanut production due to poor growth systems due to less than optimal fertilization. This is because the price of chemical fertilizers is high and difficult to obtain. This type of research is experimental research (true experiment research). This research aims to determine the effect of providing bokashi type organic fertilizer on the productivity of peanut plants. One way ANOVA test results obtained: 1) calculated F value of 4.915 with a significant value of 0.019 for the number of fruits, 2) calculated F value of 4.936 with a significant value of 0.019 for gross weight, 3) calculated F value of 6.149 with a significant value of 0.009 for net weight. Based on these data, it is known that the significant value for the number of fruit is 0.019, the gross weight is 0.019, and the net weight is 0.009, which is smaller than 0.05, so it can be concluded that the application of bokashi fertilizer has a real effect on the productivity of peanut plants (A hypogaea L.), this shows that Ha is accepted and Ho is rejected, then in this case it is necessary to proceed to the Duncan test.